FAKTOR-FAKTOR YANG MEMENGARUHI KEPUTUSAN PEMBELIAN KONSUMEN PADA E-COMMERCE LAZADA DI BEKASI - WEDANAJI PRASASTYO, KLEMENS; AZARAH, AISYAH SAFANI (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2024)
The purpose of this researchis to determine influence of Brand Awareness, Perceived Quality, Brand Association, Brand Loyalty on Purchase Decisions among Lazada e-commerce users in Bekasi City using primary and secondary data obtained using the results of distributing questionnaires with 5 Likert scales online.The design of this research uses descriptive and causal research. There were 250 respondents involved in this research. The sampling method uses non-probability sampling with a purposive sampling technique, because of certain characteristics, each unit in the sampling population used in this research is primary data where questionnaires are distributed to respondents. The method for analyzing data uses the Structural Equation Model using the WarpPLS version 7.0 program. The results of this research are that Brand Awareness has a positive and significant influence on Purchase Decisions. Perceived Quality has a positive and significant influence on Purchase Decision. Brand Association has a positive and significant influence on Purchase Decisions. Brand Loyalty has a positive and significant influence on Purchase Decisions.